2021
DOI: 10.1098/rsos.210608
|View full text |Cite
|
Sign up to set email alerts
|

Rate of infant carrying impacts infant spontaneous motor tempo

Abstract: Rhythm production is a critical component of human interaction, not least forming the basis of our musicality. Infants demonstrate a spontaneous motor tempo (SMT), or natural rate of rhythmic movement. Here, we ask whether infant SMT is influenced by the rate of locomotion infants experience when being carried. Ten-month-old, non-walking infants were tested using a free drumming procedure before and after 10 min of being carried by an experimenter walking at a slower (98 BPM) or faster (138 BPM) than average t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This result indicates that observing a rhythmic action without moving or synchronizing with it induces a spontaneous change in the SMT. This result is in accordance with the results of studies about the effects of physical training with rhythmic stimuli Carson et al, 1999;Hansen et al, 2021;Rocha et al, 2021). They are also in accordance with results about the effect of external constraints that show a significant effect of producing SMT while listening to a rhythmic metronome without synchronizing (Bouvet et al, 2019).…”
Section: Intrinsic and Extrinsic Factors Modulating Smt Valuessupporting
confidence: 91%
“…This result indicates that observing a rhythmic action without moving or synchronizing with it induces a spontaneous change in the SMT. This result is in accordance with the results of studies about the effects of physical training with rhythmic stimuli Carson et al, 1999;Hansen et al, 2021;Rocha et al, 2021). They are also in accordance with results about the effect of external constraints that show a significant effect of producing SMT while listening to a rhythmic metronome without synchronizing (Bouvet et al, 2019).…”
Section: Intrinsic and Extrinsic Factors Modulating Smt Valuessupporting
confidence: 91%
“…For example, in the Cambridge UK BabyRhythm longitudinal study, where infant drumming to speech and non-speech rhythmic stimuli was recorded using motion capture, Rocha et al (2021, pre-print) show that infant drumming becomes more rhythmic with age. This was particularly true when infants were drumming in a silent control condition, which mirrors previous findings that infants' spontaneous motor tempo becomes faster and more regular over the first years of life (Rocha, Southgate, et al, 2021). The Cambridge UK BabyRhythm study compared infant drumming in silence to an isochronous 2 Hz drumbeat, an isochronous 2 Hz repetition of the syllable 'ta', and naturalistic sung nursery rhymes.…”
Section: Multimodal Rhythm Perception and Production In Relation To L...supporting
confidence: 77%
“…In addition, some recent studies support the interaction of the vestibular system with the perception of auditory rhythms and the generation of rhythmic movement. Rocha et al (2021a , b) revealed that the tempo of vestibular inputs derived from caregivers’ gait determined the tempo of spontaneous movements in their infants. Also, Tichko et al (2021) succeeded in simulating the preference for auditory rhythms in infants with the neural-network model trained on combined auditory–vestibular stimulation.…”
Section: Discussionmentioning
confidence: 99%